A new species of the ghost shrimp genus Callianassa Leach, 1814 (Decapoda: Axiidea: Callianassidae) from Wakasa Bay, western Japan: the first representative of the genus from the Pacific region - Henmi, Yumi; Itani, Gyo; Osawa, Masayuki; Komai, Tomoyuki (Zootaxa, 2022)
The ghost shrimp genus Callianassa Leach, 1814 is currently represented by six taxa, of which five are known from the eastern Atlantic and only C. persica Sakai, 2005 from the Persian Gulf. In this study, a new species of Callianassa is described and illustrated on the basis of material from the subtidal soft sediments (at 26–28 m depth) in Wakasa Bay, western Japanese coast of the Sea of Japan. Callianassa ogurai n. sp. is the first species of the genus from the Pacific region. This study discusses characters differentiating the new species and other five congeneric species. Molecular phylogenetic analysis using the mitochondrial 16S rRNA gene supports the close relationship between the new species and C. subterranea (Montagu, 1808), warranting the generic assignment of the new species to Callianassa sensu stricto. We also explore the contentious taxonomic status of C. timiris (Sakai, Türkay, Beck & Freiwald, 2015).